2017
DOI: 10.1007/s12325-017-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacokinetic Interactions Between Obeticholic Acid and Caffeine, Midazolam, Warfarin, Dextromethorphan, Omeprazole, Rosuvastatin, and Digoxin in Phase 1 Studies in Healthy Subjects

Abstract: IntroductionObeticholic acid (OCA), a potent and selective farnesoid X receptor agonist, is indicated for the treatment of primary biliary cholangitis (PBC). We investigated the potential drug–drug interaction effect of OCA on metabolic CYP450 enzymes and drug transporters.MethodsFive phase 1 single-center, open-label, fixed-sequence, inpatient studies were conducted in healthy adult subjects to evaluate the effect of oral daily doses of 10 or 25 mg OCA on single-dose plasma pharmacokinetics of specific probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
2
17
0
2
Order By: Relevance
“…Despite the numerous examples of CYP downregulation in vitro, there is no clear example of CYP in vitro downregulation translating into meaningful DDIs in the clinic. The possible exceptions are 1) the effect of obeticholic acid on caffeine but not its metabolite paraxanthine (Edwards et al, 2017) and 2) the simultaneous inhibition and downregulation of CYP2D6 mediated by bupropion (Sager et al, 2017). Notably, the European Medicines Agency has reviewed a clinical package for a drug that exhibited downregulation of CYP activity both in vitro and in vivo (Hariparsad et al, 2017); however, no details of this package are publicly available at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous examples of CYP downregulation in vitro, there is no clear example of CYP in vitro downregulation translating into meaningful DDIs in the clinic. The possible exceptions are 1) the effect of obeticholic acid on caffeine but not its metabolite paraxanthine (Edwards et al, 2017) and 2) the simultaneous inhibition and downregulation of CYP2D6 mediated by bupropion (Sager et al, 2017). Notably, the European Medicines Agency has reviewed a clinical package for a drug that exhibited downregulation of CYP activity both in vitro and in vivo (Hariparsad et al, 2017); however, no details of this package are publicly available at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Although obeticholic acid was shown to inhibit CYP3A4 in vitro , a DDI study has demonstrated no clinically significant inhibition of CYP3A4 at the doses of obeticholic acid in clinical use. ( 52 ) Obeticholic acid is not expected to significantly inhibit or induce other cytochromes or drug transporters (Ocaliva product label).…”
Section: Investigational Agents For Nash and Potential Ddis In The Comentioning
confidence: 99%
“…Alternatively, we looked to a semisynthetic FXR agonist like obeticholic acid (6a-ethyl-chenodeoxycholic acid), which similarly elicits robust induction (.5-fold) of BSEP and small heterodimer partner mRNA expression in sandwich-cultured human hepatocytes (Zhang et al, 2017). But unlike chenodeoxycholic acid, clinical data are available for multidose obeticholic acid showing that it has a minimal effect on the AUC of an orally dosed BCRP or OATP probe drug (rosuvastatin) (Edwards et al, 2017). Consistent with such clinical data, Ijssennagger et al (2016) have reported that obeticholic acid (1 mM) elicits a relatively modest effect on OATP1B1 and OATP1B3 mRNA expression (vs. induction of ABCB11 mRNA) in precision-cut human liver slices.…”
Section: Studies With Fxr Agonistsmentioning
confidence: 99%